Deciphering Economic Fatwas in Muhammadiyah: A Comprehensive Qualitative Analysis from 1950 to 2017 - Ikhwandy, Ikhwandy; Apriantoro, Muhamad Subhi (UIN Sunan Kalijaga Yogyakarta, 2024)
This study examines the evolution of fatwas issued by the Tarjih and Tajdid Council the Central Executive of Muhammadiyah in the economic sector from 1950 to 2017. This topic was chosen because of the significant impact of these fatwas in shaping economic practices among the Muhammadiyah community, especially in responding to social and economic changes over the past few decades. This research uses a qualitative method by collecting data from various sources, including books, articles, journals, and official documents of the Tarjih Council. The data obtained was analyzed in depth to map the distribution of fatwas, as well as explore the theoretical foundations and arguments of scholars used in the formulation of these fatwas. In its analysis, this study adopts the theory of fiqh to understand the basis of thinking behind fatwa decisions. The results of the study show that the fatwas of the Tarjih Council and the Central Executive of Tajdid Muhammadiyah in the economic sector during the period were divided into three main areas: Social Economy, Banking, and Investment. As-Sunnah (Hadith) is the basis that is most often referred to in these fatwas. In addition, this study identifies that the opinion of the Hanafi School is more dominant compared to other schools. This research contributes to increasing the understanding of fatwas in the economic field formulated by the Tarjih Council and the Central Executive of Muhammadiyah Tajdid, as well as showing a strict and selective process in issuing fatwas, especially in the economic sector. Penelitian ini mengkaji evolusi fatwa-fatwa yang dikeluarkan oleh Majelis Tarjih dan Tajdid Pimpinan Pusat Muhammadiyah di bidang ekonomi dari tahun 1950 hingga 2017. Topik ini dipilih karena dampak yang signifikan dari fatwa-fatwa tersebut dalam membentuk praktik ekonomi di kalangan masyarakat Muhammadiyah, terutama dalam merespons perubahan sosial dan ekonomi selama beberapa dekade terakhir. Penelitian ini menggunakan metode kualitatif dengan mengumpulkan data dari berbagai sumber, termasuk buku, artikel, jurnal, dan dokumen resmi Majelis Tarjih. Data yang diperoleh dianalisis secara mendalam untuk memetakan sebaran fatwa, serta menggali landasan teori dan argumentasi ulama yang digunakan dalam perumusan fatwa-fatwa tersebut. Dalam analisisnya, studi ini mengadopsi teori fikih untuk memahami dasar pemikiran di balik keputusan fatwa. Hasil penelitian menunjukkan bahwa fatwa-fatwa Majelis Tarjih dan Tajdid PP Muhammadiyah di bidang ekonomi selama periode tersebut terbagi menjadi tiga bidang utama: Ekonomi Sosial, Perbankan, dan Investasi. As-Sunnah (Hadis) merupakan dasar yang paling sering dirujuk dalam fatwa-fatwa tersebut. Selain itu, penelitian ini mengidentifikasi bahwa pendapat Mazhab Hanafi lebih dominan dibandingkan dengan mazhab-mazhab lainnya. Penelitian ini berkontribusi dalam meningkatkan pemahaman terhadap fatwa-fatwa di bidang ekonomi yang dirumuskan oleh Majelis Tarjih dan Tajdid Pimpinan Pusat Muhammadiyah, serta menunjukkan adanya proses yang ketat dan selektif dalam mengeluarkan fatwa, khususnya di bidang ekonomi.